OPTIMIZATION OF INFRASTRUCTURE PROJECT PRODUCT PARAMETERS - Nikolay Vereshchaka (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the research is the means of determining the optimal set of parameters for the products of infrastructure projects. The aim of the study is to increase the efficiency of the implementation of infrastructure projects through the use of the developed model for substantiating the optimal parameters of their products. To achieve this goal, the following tasks have been solved: determination of the main options for "autonomy" of infrastructure projects; formalization of the dependences of the time, value and economic characteristics of infrastructure projects on the parameters of their products (infrastructure object) and the development of a conceptual model for optimizing these parameters; development of a mathematical model for optimizing the parameters of products of this category of projects. The following methods are used: system analysis, functional analysis, operations research. Results: it was found that the parameters of the product of infrastructure projects, on the one hand, ensure its commercial relevance, on the other hand, they determine the characteristics of the project (cost, risks, life cycle duration, etc.), which forms a complex system of requirements and restrictions for product parameters. As a result of the study, a conceptual and corresponding mathematical model for optimizing the parameters of an infrastructure project product has been developed for two situations: 1) for a situation of an "autonomous" infrastructure project, in which the infrastructure object being created does not imply commercial use, or its creation and commercial use is carried out within the framework of one project; 2) for a situation of two interconnected by means of a project infrastructure object - the creation of an object and its management (commercial use). Modeling is based on formalized dependences of the value, time and economic characteristics of the project on the parameters of its product. Conclusions: the model allows to determine at the initial stage of project development, within the possible range of variation, that set of parameters of its product that provides maximum value for stakeholders both when creating an infrastructure object and in the future when managing (operating) it.